17 State and trait interoception is disrupted in functional seizures. (28th May 2019) - Yogarajah, M; Koreki, A; Agrawal, N; Cope, S; Eilon, T; Van Praag, C Gould; Garfkinel, S; Critchley, H; Mula, M; Edwards, M
Abstract : Objectives: The continuity and integrity of a conscious sense of self, is proposed to be dependent upon the control of internal physiological state and its predictive representation through interoception, that is, the sensing of internal bodily changes. We investigated dissociation, interoception and their relationship, in patients with functional seizures (FS), before and after a stressor intervention. Methods: 41 participants with functional seizures (FS) and 30 age/gender matched healthy controls (HC) were assessed with the somatoform dissociation questionnaire (SDQ20), multi-scale dissociation inventory (MDI), and the state and trait anxiety inventory (STAI). Standardized measures of interoceptive sensibility, accuracy, and awareness were acquired with the Porges Body Perception Questionnaire (PBPQ), and heartbeat discrimination (HDT), tracking (HTT) and time-tracking tasks (TTT), before and after a cold pressor test. Continuous non-invasive blood pressure monitoring was carried out before, during and after the cold pressor test. Interoceptive trait (ITPE) and state (ISPE) prediction errors, that is, the discrepancy between interoceptive accuracy and the PBPQ (trait), and trial-by-trial confidence estimates (state), were calculated before and after the cold pressor test respectively, for HTT and HDT. An autonomic prediction error (APE), or the discrepancy between the reported increase in pain and the change in blood pressure after the cold pressor, was also calculated. Results: Patients with FS differ significantly from HC for HTT, ITPE and ISPE suggesting that they are overall less interoceptively accurate and aware than HC. This is confirmed by a correlation between APE and the ISPE derived from the HDT task (r=0.359, p=0.033) in FS subjects only, after correcting for state anxiety and duration of cold pressor. Furthermore, in FS patients only, ITPE scores, adjusted for trait anxiety, correlated with SDQ-20 and MDI-depersonalization scores for both HTT (r=0.378, p=0.008; r=0.408, p=0.005) and HDT (r=0.364, p=0.011; r=0.281, p=0.044). All results survived FDR correction at a 0.05 threshold. Conclusions: These findings demonstrate that state and trait interoception are disrupted in patients with FS. The severity of the disruption in trait interoception correlates with measures of dissociation, such that the bigger the ITPE, the more severe are the dissociative traits. Similarly, the greater the ISPE, the larger the discrepancy between subjective symptoms and objective physiological changes, after a stressor intervention. Our findings suggest that the selective disruption of interoceptive processing is both a potential predisposing and precipitating factor in FS.